Chondroitin Sulfate as a Lysosomal Enhancer Attenuates Lipid-Driven Inflammation via Lipophagy and Mitophagy - Ting Sun; Huimin Lv; Huarong Shao; Xiuhua Zhang; Anqi Wang; Wei Zhang; Fei Liu; Peixue Ling (Marine Drugs)
Non-alcoholic steatohepatitis (NASH), a progressive liver disease characterized by lipid accumulation and chronic inflammation, lacks effective therapies targeting its multifactorial pathogenesis. This study investigates marine-derived chondroitin sulfate (CS) as a multi-organelle modulator capable of regulating lipid metabolism, oxidative stress, and inflammation in NASH. By employing subcellular imaging and organelle-specific labeling techniques, we demonstrate that CS restores lysosomal acidification in a NASH model, enabling the reduction of lipid droplets via lysosomal–lipid droplet fusion. Concurrently, CS upregulates dynamin-related protein 1 (DRP1), driving mitochondrial terminal fission to spatially isolate reactive oxygen species (ROS) segments for mitophagy, thereby reducing ROS levels. Notably, pharmacological inhibition of lysosomal activity using chloroquine or bafilomycin A1 abolished the therapeutic effects of CS, confirming lysosomal acidification as an essential prerequisite. Collectively, these findings reveal the potential of CS as a therapeutic agent for NASH and provide critical insights into the subcellular mechanisms underlying its protective effects, thus offering a foundation for future research and therapeutic development.